Pengaruh Program BBM (Bekal Buatan Mama) terhadap Pemenuhan Gizi Anak di Taman Kanak-Kanak Suka Haji Cileunyi - Siti Taghsya Mumtazayyanah; Dwi Undayasari (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to determine the effect of the BBM (Bekal Buatan Mama) program on the fulfillment of early childhood nutrition at Suka Haji Kindergarten, Cileunyi. The BBM program is an initiative that encourages active participation of parents, especially mothers, in preparing healthy food for children as an effort to increase balanced nutritional intake from an early age. This study used a quantitative method with a pre-experiment design, namely a one-group pretest-posttest design involving 30 children as research subjects. Data were collected through direct observation and analysis of daily lunch menus based on balanced nutrition guidelines from the Indonesian Ministry of Health. The results of the study showed a significant improvement in the quality of children's nutritional intake in the group that participated in the BBM program. This finding suggests that parental involvement in food provision through the BBM program has a positive impact on meeting the nutritional needs of early childhood. It is recommended that similar programs be adopted more widely in early childhood education settings to support optimal growth and child development.